Dinamika Pendidikan Islam Pasca Kemerdekaan Indonesia: Antara Kebijakan, Transformasi Institusi, dan Peran Tokoh Pembaru - Sakti Putra Mahardika; Dzulkifli Hadi Imawan; Sri Haningsih (Universitas Cokroaminoto Yogyakarta, 2026)
The Islamic education in Indonesia have been surpassed many improvement phases. This research would present systematic the imagine of Indonesia Islamic education in policies, institution, and figure contributions. In this study, qualitative methods that based on literature review with analysis content are combined. The Old Order era was marked by the stabilization, adaptation, and transition of the non-classical to classical system of Islamic education. During the New Order era, the government recognized madrasahs as formal institutions equal to other Islamic higher education initiatives. The Reformation era saw modernization efforts in madrasahs, Islamic boarding schools, and Islamic universities. In addition to strengthening Islamic education through new laws, progress was inextricably linked to the contributions of educational figures from the ranks of ulama, intellectuals, and bureaucrats. The conclusion suggests that synergy between policy and leadership is key to the transformation of Islamic education in Indonesia from independence to the reform era.